Disparitas Putusan Hakim Dalam Perkara Nomor 122/Pid.B/2005/PN.PYK Dengan Putusan Nomor 57/PID/2006/PT.PDG - Putra, Nugraha Azel; Effendi, Erdianto; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In 2005 at Payakumbuh City, West Sumatra threre was an uproar case, a premeditated murder of a Japanese citizen named Tomoko Ishizawa aka Mochhi. In this case there was a disparity the country court decision and the high court decision, which is the decision numberd 122/Pid.B/2005/PN.Pyk convicted 20 years in prison while the decision numbered 57/PID/2006/PT.PDG convicted the death penalty. The problems are how the judge consideration in deciding conviet for the first level and the higher one, and whether factor that cause the dicision disparities in the decision numbered 122/Pid.B/2005/PN.Pyk and the decision numbered 57/PID/2006/PT.PDG.After the research by using descriptive or normative legal research, data sourees supported by three legal matcrials which is primary data, secondary data and tertiary data, while the data collection teehniques were the study of literature, decisions and legislation relating to the discussion. After the data were collected then analyzed qualitatively to address problems in this script and the conclusions were deductively taken.Based on the results of research that the judge consideration of the high court focused on the judgment against the defendant and denied the considerations that relieve the defendant in the country court. The high court judges convicted the death penalty based on the maximum sentence of Article 340 of the KUHP, while country court judges convicted 20 years in prison based on the minimum sentence of Article 340 the KUHP. Then the factors that lead to disparities in the decision numbered 122/Pid.B/2005/PN.Pyk and the decision numbered 57/PID/2006/PT.PDG were grouped into 3 sections based on the sources which is the legal system and the philosophy of punishment, the of the judge and the defendant.